Analysis of Tafsir verse verse Consumption of the Qur'an on Sharia Economic Development - Iqbal, Muhammad; Sunandar, Heri (International Journal Labs, 2023)
All economic activities originate from human physical needs to be able to continue living in this world. All the needs for survival will be worked on by themselves, but when the needs for life cannot be met alone, then there is social interaction in meeting the needs of life among humans. This interaction actually represents the interaction of demand and supply, the interaction of consumption and production, so that the market emerges as a container for this economic interaction. In Islam it is explained that the earth with everything in it is the mandate of Allah SWT to humans to be used as well as possible for the welfare of Muslims. While humans have two functions in this world, namely as servants of God whose duty is to worship Him and as caliphs whose duty is to prosper and prosper God's earth. One of the uses that has been given to man as the caliph of God is economic activities in general and consumption activities in particular. Islam teaches people to use the right foundation in order to gain pleasure from Allah in carrying out their functions as caliph.